Power Quality Improvement in Commercial and Industrial Sites: An Integrated Approach Mitigating Power Oscillations - Dos Santos Alonso, Augusto Matheus; De Oro Arenas, Luis [UNESP]; Bonaldo, Jakson Paulo; Olímpio Filho, Jose De A. [UNESP]; Marafão, Fernando Pinhabel [UNESP]; Paredes, Helmo K. Morales [UNESP] (My University, 2024)
This paper introduces a novel control strategy for multifunctional grid-tied inverters in industrial/commercial power systems, aiming to address the compensation of instantaneous power oscillations. The proposed strategy is derived from the Conservative Power Theory, which offers the ability to extract and analyze oscillating power terms directly in the abc frame. To demonstrate the efficacy of the proposed strategy, simulation results are presented, considering a scenario with a three-phase multi-functional grid-tied inverter with an LCL filter operating in a laboratory scale prototype. The power system includes various types of loads, such as linear, non-linear, unbalanced loads and a three-phase induction motor with capacitive compensation. Simulation results show the effectiveness of the proposed strategy in coping with the active power dispatch provided by the inverter, concomitantly ensuring that the induction motor operates with constant torque, as well as that the industrial/commercial electric system operates with improved power quality. Furthermore, the proposed strategy is also validated by means of experimental results obtained from a 3.6 kVA inverter prototype. The experimental findings affirm that the compensation of the targeted oscillating power terms is successfully achieved. Such a validation underscores the practical viability of applying the proposed strategy to real-world scenarios.
Keywords: Conservative power theory; induction motor; instantaneous power oscillations; multifunctional inverters; power factor; power quality